2022
DOI: 10.1021/acssuschemeng.2c02098
|View full text |Cite
|
Sign up to set email alerts
|

Low-Cost CuX Catalyst from Blast Furnace Slag Waste for Low-Temperature NH3-SCR: Nature of Cu Active Sites and Influence of SO2/H2O

Abstract: A series of Cu-exchanged zeolite NaX (derived from blast furnace slag) catalysts were synthesized by an ionexchanged method. The low-temperature catalytic activity and SO 2 or/and H 2 O resistance of the catalysts were studied as well. The results found that the Cu(N)X catalyst exhibited excellent lowtemperature selective catalytic reduction (SCR) activity, whose NO conversion was nearly 100% at ca. 175 °C and remained stable, while the Cu(C)X catalyst showed the poorest catalytic performance. When SO 2 and H … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(10 citation statements)
references
References 58 publications
0
10
0
Order By: Relevance
“…The types of salt species and intermediates lead to bad NH 3 -SCR activity. 34 In this study, it can be known from XPS that after adding La (CeCrLaCu/TiO 2 ), Cu 2+ decreases and Cu+ increases, so it can reduce the formation of sulfate with sulfuric acid, thereby inhibiting poisoning. Hydrothermal stability refers to the property of catalytic cracking catalysts in industrial application.…”
Section: Introductionmentioning
confidence: 83%
See 1 more Smart Citation
“…The types of salt species and intermediates lead to bad NH 3 -SCR activity. 34 In this study, it can be known from XPS that after adding La (CeCrLaCu/TiO 2 ), Cu 2+ decreases and Cu+ increases, so it can reduce the formation of sulfate with sulfuric acid, thereby inhibiting poisoning. Hydrothermal stability refers to the property of catalytic cracking catalysts in industrial application.…”
Section: Introductionmentioning
confidence: 83%
“…For example, the metal element Cu easily reacts with sulfuric acid generated by H 2 O and SO 2 , resulting in the lack of active components and additives, and the sulfate species generated on the surface of the catalyst consumes the active Cu 2+ species and occupies the main active sites, thereby reducing nitric acid. The types of salt species and intermediates lead to bad NH 3 -SCR activity . In this study, it can be known from XPS that after adding La (CeCrLaCu/TiO 2 ), Cu 2+ decreases and Cu+ increases, so it can reduce the formation of sulfate with sulfuric acid, thereby inhibiting poisoning.…”
Section: Introductionmentioning
confidence: 90%
“…On this basis, a series of copper exchange zeolite NaX catalysts using blast furnace slag (BFS) as raw material were prepared by ion exchange method, the results showed that Cu(N)X catalyst exhibited excellent low temperature selective catalytic reduction activity, and the NO conversion rate was close to 100% at 175°C and remained stable. [4,5] Ren et al proposed an indirect CO 2 storage method using blast-furnace slag as raw material, and the results showed that the net CO 2 emissions could be reduced by 36 kg for every 1000 kg of blast-furnace slag treated. [6] Metallurgical slag has obtained good results in terms of catalyst and carbon capture.…”
Section: Introductionmentioning
confidence: 99%
“…Nitrogen oxides (NO x ) are mainly emitted from automobile exhaust gas and flue gas of industrial combustion of fossil fuels and can cause photochemical smog, acid rain, ozone depletion, and greenhouse effects, thus leading to hazardous effect on the environment and human health. Several promising catalytic technologies, such as NO x storage and reduction (NSR) and selective catalytic reduction (SCR) of NO x , have been developed to reduce NO x emissions. Among them, selective catalytic reduction of NO x by NH 3 is the most widely used technology . However, this approach comes with issues such as NH 3 slip and “white powder” formation, which limits its practical application. Therefore, research has also focused on the development of new technology or using alternative reductants to remove NO x by the SCR process.…”
Section: Introductionmentioning
confidence: 99%